A comparative study of room temperature ionic liquids and their organic solvent mixtures near charged electrodes. (14th September 2016) - Vatamanu, Jenel; Vatamanu, Mihaela; Borodin, Oleg; Bedrov, Dmitry
Abstract: The structural properties of electrolytes consisting of solutions of ionic liquids in a polar solvent at charged electrode surfaces are investigated using classical atomistic simulations. The studied electrolytes consisted of tetraethylammonium tetrafluoroborate (NEt4 -BF4 ), 1-ethyl-3-methylimidazolium tetrafluoroborate (c2 mim-BF4 ) and 1-octyl-3-methylimidazolium tetrafluoroborate (c8 mim-BF4 ) salts dissolved in acetonitrile solvent. We discuss the influence of electrolyte concentration, chemical structure of the ionic salt, temperature, conducting versus semiconducting nature of the electrode, electrode geometry and surface roughness on the electric double layer structure and capacitance and compare these properties with those obtained for pure room temperature ionic liquids. We show that electrolytes consisting of solutions of ions can behave quite differently from pure ionic liquid electrolytes.